Mentoring in learning development - Silvina Bishopp-Martin; Ursula Canton; Jane McKay; Chenée Psaros; Alicja Syska; Samantha Thomas (Journal of Learning Development in Higher Education, 2023)
Learning Development is still a relatively young field (Syska and Buckley, 2022), and despite a growing body of research, it remains strongly practice-oriented. This means that experience, in this case of individual Learning Developers, takes an even more central place than it does in more established fields, and sharing this experience through mentoring takes on a central role. This is why the mentoring working group has developed a Learning Development focused ALDinHE Mentoring Scheme, together with a Certified Mentor recognition that helps experienced mentors be recognised for their contribution to growing and sharing LD knowledge. This mini keynote briefly introduced the Mentoring Scheme and the CeM recognition before exploring the role mentoring can play in the professional development of Learning Developers with the audience.